Oh, if the street, the sidewalk and the square were public! Uses of public space in Ceará-mirim, Brazil - Silva, Kelson de Oliveira; Monteiro, Sebastião Lopes (Geosaberes; Vol 8 No 14 (2017): Jan - Apr, 2017)
The work in question is the result of PIBIC Jr. project, developed with CNPq scholarship support, in partnership with FAPERN, run by public schools teaching the SEEC/RN. The research studied the uses and the physical condition of the streets and public leisure facilities, identifying the agents responsible for the privatization of these public goods. The methodological procedures used were: a) questionnaires to the population of Ceará Mirim, residing near public parks and recreational facilities; b) conducting interviews to local merchants also installed close to such property for public use; c) and photographic documentation in order to verify the physical condition of public squares and public leisure facilities. In analyzing the issue of privatization of public space, research contributed to the debate this issue, highlighting the conditions of public squares and Ceará Mirim leisure equipment. It was found that the city of Ceará Mirim presents uneven distribution and poor maintenance of its public squares and its leisure facilities, which is compromising the quality of life of its citizens to injure the right to leisure and the free access and use of public place.
Keywords: Privatização; Praças públicas; Equipamentos de lazer.